Status of Human Elephant Conflict (HEC) in the Nilgiri Biosphere Reserve:A Case Study from the Bandipur National Park, Karnataka, India - Lingaraju, H. G.; Venkataramana, G. V. (Indian Forester, 2016)
An assessment of human elephant (Elephas maximus) conflict was carried out in Bandipur National Park, Karnataka during 2012-13. The available forest department records related to conflict since 2007 on wards were also used for analysis. Primary conflicts included crop raiding, human casualties and elephant mortality. Crop damage was intense in the months of December and more than twenty cultivated plant species have been damaged. Elephants were killed near farmlands by farmers in defence of their crops. Among dead elephants males were 35.89% and females were 64.09%, their age class ranges from 1 to 38 years. Incidents took place normally in rainy (50%) and winter (42%) seasons as crop maturity correlates those seasons. The present investigation also revealed, 31 human casualties, of which thirteen human deaths and eighteen injuries were recorded. Male victims, were aged between 21-70 years, females were between 25 - 60 years old. Casualties for men was higher than female, about 79% of these incidents were caused by bulls. Mitigation measures presently adopted involve traditional drive away techniques including making noise by shouting, drum beating, bursting fire crackers and bursting fire crackers. Forest department also erected solar fence and EPTs along the forest boundary to prevent conflict.